2008
DOI: 10.1111/j.1439-0434.2008.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase CHIT36 from Trichoderma harzianum Enhances Resistance of Transgenic Carrot to Fungal Pathogens

Abstract: Microbial endochitinase CHIT36 is one of the lytic enzymes secreted by Trichoderma harzianum that exhibits antifungal activity in vitro. To evaluate its activity when expressed in planta, a plasmid containing chit36 gene under the control of CaMV 35S promoter and the nptII selection gene were introduced into polyethylene glycol (PEG)-treated carrot (Daucus carota L.) protoplasts. The transgenic plants expressing CHIT36 were used in resistance assays to evaluate their susceptibility to fungal pathogens. Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Expression of certain endochitinase encoding genes from Trichoderma spp. in plants has been shown to improve their defense response against various fungal pathogens ( Baranski et al 2008;Bolar et al 2000Bolar et al , 2001Dana et al 2006;Distefano et al 2008;Emani et al 2003;Lorito et al 1998). Previous work from our laboratory has demonstrated that cotton plants transformed with a gene encoding 42 kDa endochitinase from T. virens showed a high level of resistance to infection by Rhizoctonia solani and Alternaria alternata (Emani et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Expression of certain endochitinase encoding genes from Trichoderma spp. in plants has been shown to improve their defense response against various fungal pathogens ( Baranski et al 2008;Bolar et al 2000Bolar et al , 2001Dana et al 2006;Distefano et al 2008;Emani et al 2003;Lorito et al 1998). Previous work from our laboratory has demonstrated that cotton plants transformed with a gene encoding 42 kDa endochitinase from T. virens showed a high level of resistance to infection by Rhizoctonia solani and Alternaria alternata (Emani et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Genetic engineering for enhanced disease resistance in carrot has been previously shown to be partially successful through the expression of a single pathogenesis-related (PR) protein, such as chitinase, -1,3 glucanase, thaumatinlike protein or peroxidase (Punja and Raharjo 1996;Melchers and Stuiver 2000;Chen and Punja 2002;Punja 2005;Jayaraj and Punja 2007;Baranski et al 2008;Wally et al 2009), or using a combination of two genes (Melchers and Stuiver 2000;Jayaraj and Punja 2007;Wally et al 2009). These approaches have not, however, provided broad-spectrum resistance towards a wide range of pathogens.…”
Section: Introductionmentioning
confidence: 98%
“…The homologous chit42 gene from T. virens was able to enhance resistance against R. solani when it was expressed in rice (Shah et al, 2009). Other Trichoderma chitinase genes have been used to generate transgenic plants resistant to fungal diseases: (i) tobacco cell cultures expressing the T. harzianum endochitinase chit40 gene released the enzyme into the medium and were able to inhibit the conidial germination of the post-harvest pathogen Penicillium digitatum (Brants & Earle, 2001); (ii) transgenic cotton plants expressing the T. virens endochitinase gene Tv-ech1 showed significant resistance to A. alternata and R. solani and a rapid and greater induction of ROS, followed by modulation of the expression of several defence-related genes and the induction of the terpenoid pathway (Emani et al, 2003;Kumar et al, 2009); (iii) the expression of the endochitinase chit36 gene of T. harzianum in carrot significantly enhanced tolerance to A. radicina and B. cinerea (Baranski et al, 2008).…”
Section: Transgenic Plants Expressing Trichoderma Genesmentioning
confidence: 99%